The rationality of scientific reasoning in the context of pursuit: drawing appropriate distinctions - Kosolosky, Laszlo; Šešelja, Dunja; Straßer, Christian (PHILOSOPHICA, 2012)
The aim of this paper is to disambiguate between different notions of pursuit worthiness regarding scientific inquiries. To this end we propose a unifying pattern of pursuit worthiness: It is rational for Y to pursue X if and only if pursuing X is conducive of the set of goals Z. By showing in which ways variables X, Y, and Z can be changed, we present different notions of pursuit and pursuit worthiness. With respect to variable X, we distinguish the pursuit of scientific theories, epistemic objects, and technological developments. With respect to variable Z, we distinguish between epistemic and practical pursuit worthiness. Finally, with respect to variable Y, we distinguish between individual and communal pursuit worthiness. By means of these distinctions we are able to explicate some of the major ambiguities underlying the concept of pursuit of pursuit worthiness, as well as to shed light on some confusions in philosophical literature that have resulted from their neglect.